Prototipo de aplicación web para seguimiento de procesos de selección de personal en la empresa LojaSoft Solutions - Cañadas Naula, Michelle Stefania (2023)
In recent years ICTs have facilitated the optimization of procedures in companies, especially the human resources area has benefited from tools that allow automating the recruitment process, while the selection stage has been neglected technologically speaking, this leads to the use of unobjective methods for hiring new workers by the need to fill job vacancies, which directly affects negative results for businesses. In the city of Loja, the existence of this problem was observed in small and medium-sized companies, as is the case of LojaSoft Solutions, which did not have a support tool for its personnel selection processes, presenting problems of inconsistency of information and a high demand of time to perform the associated tasks. This project seeks to solve these difficulties through the development of a software solution to follow up the selection processes. The project followed the XP agile development methodology, in the planning phase combined techniques were applied for the elicitation of requirements, such as the interview technique and passive observation, which allowed the elaboration of the initial documentation of system requirements in the IEEE-830 standard, so that each requirement became a user story. In the design phase the entity-relationship model and the architecture were established based on the client-server and REST models, then in the coding phase the prototype was implemented using the TypeScript programming language with the Angular framework for the frontend and the Python programming language with the Django RestFramework framework for the backend, additionally bootstrap libraries were used as support for the visual part and MySQL for database management. Finally, unit tests were performed to the critical services of the backend and black box tests to the functional requirements with high and medium priority of the frontend in a simulated test environment for the company LojaSoft Solutions. As a result, it is evident that the implementation of the developed prototype has a positive influence on the company LojaSoft Solutions, facilitating the persistence and organization of information, which significantly reduces data inconsistency. In addition, it allowed optimizing the time invested in a personnel selection process due to the functionality of reports and the elimination of time restrictions to perform the tests, likewise, it is corroborated that the costs of mobilization and telephone calls were considerably minimized. Key words: Software development, XP methodology, personnel selection.